Apple Intrinsic Factors Modulating the Global Regulator, LaeA, the Patulin Gene Cluster and Patulin Accumulation During Fruit Colonization by Penicillium expansum - Kumar, Dilip; Tannous, Joanna; Sionov, Edward; Keller, Nancy; Prusky, Dov (Frontiers in Plant Science, 2018)
The mycotoxin patulin is produced in colonized tissue by Penicillium expansum during storage of apples and is significantly affected by environmental factors that contribute to its accumulation. Few reports have, however, examined the effect of natural intrinsic factors associated with the fruit on the production of patulin. Here we find that with advancing maturity, Golden Delicious apples show increased concentrations of total soluble solids (TSS) from 14 to 17% associated with the increased expression of the global transcription factor involved in regulation of secondary metabolite biosynthesis in filamentous fungi, laeA expression and patulin accumulation. However, the apple cultivar Granny Smith, with similar TSS values but differing in pH levels and malic acid concentrations, showed reduced expression levels of laeA and the patulin biosynthesis gene cluster (pat genes) and patulin accumulation, suggesting a complexity of host factors contribution to patulin accumulation during P. expansum colonization. To start elucidating these apple intrinsic factors, we examined their in vitro impact on laeA and pat gene expression concomitant with patulin synthesis. Increasing sucrose concentrations from 15 to 175 mM repressed laeA and pat gene expression and patulin production. However, this affect was modified and often reversed and sometimes accentuated by changes in pH, or the addition of malic acid or the major apple phenolic compounds, chlorogenic acid and epicatechin. While the increase in malic acid from 0 to1% increased laeA and pat gene expression, the decrease in pH from 3.5 to 2.5 reduced their expression. Also the increased laeA and pat genes expressions at increasing epicatechin concentrations from 0 to 1mM, was reversed by increasing sucrose concentrations, all together suggesting the complexity of the interactions in vivo. .